"The Islamic Party of Kenya": An Anatomy of an Ethnic Party - Yaskirevitch, Itay (Jama'a: an Interdisciplinary Journal of Middle East Studies, 2002)
In early 1992, the announcement of a multi-party election in Kenya reshaped the national political arena and enabled the establishment of an Islamic party. While this party gained much Muslim support in the coastal city of Mombassa, it was later disqualified for elections and lost its place in the official political arena under the official pretext that no religious party was allowed to stand for election. Nevertheless, the party still continued to draw an important Muslim public, which demanded more significant political representation. This partisan activity invoked a lively debate among government officials, local journalists, and researchers who mainly presented the Muslim party as fundamentalist and radical. In this article, I show that such a conventional narrative is misleading. Based on contemporary research on ethnic and religious identities in Africa, I demonstrate how the activities of the Islamic party mirror ethnic divisions in this country's political-cultural framework.